Tensile Strength of Natural Fiber in Different Type of Matrix - Taufiq Saidi; Muttaqin Hasan; Zahra Amalia (Graduate Program of Syiah Kuala University, 2022)
In recent years, the used of product based with low environmental impact has become one of the considerations in the construction structure. Attention of the researchers towards the development of natural material has been increasing. The use of natural fibers as composite materials for strengthened structure have been studied. However, natural fibers are influenced by the hydrophilic nature and its specific morphology. Thus, research related to the natural fiber composite materials still needs to be explored. This study aims to evaluate the tensile strength of natural fiber composite materials based on the type of fiber, fiber layer used and its type of resin according to ASTM D3039. The results show that type of fiber, fiber layer used and its type of resin in the composite matrix considerably affects its tensile strength performance.